EFISIENSI EKONOMI FAKTOR PRODUKSI PADA USAHATANI BROKOLI DI KELURAHAN KAKASKASEN - Juliana R. Mandei; Christy P. Tuwongkesong (Sam Ratulangi University, 2015)
The study aims to determine the efficiency of use of factors of production in Broccoli farming. Research carried out on all Broccoli farmers in Kakaskasen Village. Data were analyzed using multiple linear regression analysis with a model of Cobb-Douglas production function. The results showed that the uses of factors of production (land, seed, fertilizer and labor) have given a significant effect simultantly on the production of broccoli in Kakaskasen Village. Technically, the use of production factors of seed, fertilizer, NPK fertilizer and labor is efficient, while the use production factor of land is not efficient yet and Urea fertilizer production factor is not efficient. Economically, the use of production factors of land, seed, fertilizer, NPK fertilizer and labor have not been efficient yet, while the use of factors of production of urea is not efficient.